Reconstruction of the Tibial Stump After Fibulectomy - Bezsmertnyi YO; Veremii OA; Shevchuk VI; Bezsmertnyi OY (Orthopedic Research and Reviews)
Yurii Oleksiiovych Bezsmertnyi, Oleg Andriyovych Veremii, Viktor Ivanovych Shevchuk, Olexander Yuriyovych Bezsmertnyi Scientific Department, Scientific and Research Institute of Rehabilitation of National Pirogov Memorial Medical University, Vinnytsia, UkraineCorrespondence: Viktor Ivanovych Shevchuk, Email shevchukndiri@gmail.comAbstract: The formation of a functional tibial stump after combat injuries with extensive tissue damage is sometimes difficult. We describe a case of reconstruction of the tibial stump after a mine-blast injury. In this case, the fibula was completely removed as a result of fracture, and the tibia was amputated at the border of the upper and middle thirds. To create a stable platform with a larger bearing surface area and reduce the load on the distal fossa, the Ilizarov method was used. For the first time, the area of the bearing surface of the tibia stump was increased by more than 2 times in the case of the removed fibula. Thanks to the original surgery technique, the mushroom shape of the stump end was also obtained for the first time. In the process of prosthetics, this geometry actually increases the bearing surface area and has advantages over the Ertl technique, where the cylindrical end of the stump due to muscle atrophy and thinning of the fibro-skin lining can lead to bursitis and even ulcers. The spherical shape of the stump end causes less soft tissue trauma, increases the load-bearing capacity and durability of the results. According to the data of the GaitRite system, the walking performance in the long-term period practically corresponded to that of a healthy person. The technique of the operation is described in detail, including petal decortication, two oblique corticotomies of the tibia, formation of bone and periosteum fragments, distraction. The result is a highly functional stump with the possibility of using end support and full prosthetics. The proposed technique can be used in reconstructive operations on the tibia and femur stumps.Keywords: reamputation, distraction, absence of the fibula, increase in the area of the end of the stump, Ilizarov method